Two-time recurrence of a right atrial myxoma - Kumary, V. Sudha (Proc (Bayl Univ Med Cent), 2015)
We report a case of a second recurrence of a right atrial myxoma in a 38-year-old woman who had surgical excision in March 2008 and excision of a recurrence in August 2012. She presented with a similar clinical picture in December 2014 and again underwent surgical excision. The case is unusual both for its location in the right atrium and its multiple recurrences in a sporadic form without any sign of the myxoma complex.